2001
DOI: 10.1128/jcm.39.7.2453-2457.2001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Variable Number Tandem Repeat and IS 6110 -Restriction Fragment Length Polymorphism Analyses for Discrimination of High- and Low-Copy-Number IS 6110 Mycobacterium tuberculosis Isolates

Abstract: The present study was designed to evaluate the use of variable number tandem repeat (VNTR) and IS6110-restriction fragment length polymorphism (RFLP) analyses in combination as a two-step strategy for discrimination (as measured by the Hunter-Gaston Discrimination Index [HGDI]) of both high-and lowcopy-number IS6110 Mycobacterium tuberculosis isolates compared to IS6110-RFLP alone with an unselected collection of isolates. Individually, IS6110-RFLP fingerprinting produced six clusters that accounted for 69% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 41 publications
0
47
0
1
Order By: Relevance
“…2). Therefore, the 16-locus panel is less discriminatory than RFLP for molecular typing of PETRA lineage strains, although it still may have value for identifying epidemiological links (8,74). A 24-locus MIRU-VNTR panel has recently been reported to separate each of many different CAS spoligotypes (6).…”
Section: Petra Lineage Consensus Miru-vntr Typing Profilementioning
confidence: 99%
“…2). Therefore, the 16-locus panel is less discriminatory than RFLP for molecular typing of PETRA lineage strains, although it still may have value for identifying epidemiological links (8,74). A 24-locus MIRU-VNTR panel has recently been reported to separate each of many different CAS spoligotypes (6).…”
Section: Petra Lineage Consensus Miru-vntr Typing Profilementioning
confidence: 99%
“…Some authors have found it to show a discriminatory power equivalent to that of RFLP and have considered it an alternative to IS6110-RFLP for epidemiological purposes [4][5][6][7] . However, other authors have found limitations in its discriminatory power and incomplete correlation with the RFLP analysis [8][9][10] , indicating that MIRU analysis should be combined with an additional genotyping method [10][11][12][13] . We compared the MIRU-12 version and IS6110-RFLP in independent samples in the context of molecular epi- Materials and Methods…”
Section: Introductionmentioning
confidence: 99%
“…VNTR typing (10), is a more rapid method, requires little culture growth, provides easy-to-compare numerical data, and can be performed by standard agarose gel electrophoresis or, alternatively, developed as a high-throughput system. Mycobacterial interspersed repetitive unit (MIRU) typing utilizes 12 VNTR loci and has been found to have similar discriminatory power to RFLP depending on the sample population, particularly in cases where isolates have zero to five copies of the IS6110 element, such as with M. bovis strains (2,7,15,18,25). It is plausible that MIRU typing may become the predominant method of choice for TB genotyping (15).…”
mentioning
confidence: 99%